AGE DIFFERENCES OF THE EРSHTEIN – BARR VIRUS INFECTIOUS MONONUCLEOSIS - A. L. Bondarenko; M. V. Savinykh; N. A. Savinykh; T. I. Kaluzhskikh; N. V. Khlebnikova; L. V. Malkova; N. V. Ryabova (Журнал инфектологии)
During the dynamic observation, clinical and laboratory results of 194 patients with infectious mononucleosis of Eрstein-Barr etiology of different age groups were summarized. In the comparative aspect, the identity of the symptoms is revealed. Along with this, the dependence of some clinical and laboratory parameters on the age of patients was found. Patients with preschool and school age often registered febrile fever, decreased appetite, raids on tonsils, the first appeared «snoring in a dream», hepatosplenomegaly. For teenagers and adults, icterus, a pronounced mononuclear response and cytolysis syndrome are more common.